Online food nutrition labelling in the UK: how consistent are supermarkets in their presentation of nutrition labels online? - Stones, Catherine (Public health nutrition, 2016)
To evaluate consistency levels of nutrition labelling on supermarket websites. This is a comparative, quantitative study examining page position, content and design of nutrition labels on own-brand and branded products. Online and in-store nutrition labels were examined, categorised and analysed to discern variety of label designs used and consistency between online and in-store labelling. Five large online food retailers in the UK. Nutrition labels displayed on 100 webpages were examined for twenty branded and own-brand products. Equivalent labels on in-store packaged products were also examined. Eight different combinations of nutrition label designs were found. The online supermarket sites were found to use from three to six of these label combinations across the sample. The consistency level between online and in-store package labels ranged from 25 % to 90 %. In many cases the nutrition label required scrolling to view and in all cases items could be purchased without the label being visible from the search result listings. The main recommendation of the paper is that online nutrition labelling needs to be much more consistently presented than is currently practised, both within each website and between online and in-store experiences. Particular attention should be made to polychrome colour and the inclusion of summary graphics. Designers should also ensure visibility of the label and raise its vertical page position. The paper also proposes additional expansion of the use of nutrition information online, using nutrition values as database fields in search criteria and checkout aggregation reporting.